Potential diagnostic markers for disseminated intravascular coagulation of sepsis - Iba, Toshiaki; Ito, Takashi; Maruyama, Ikuro; Jilma, Bernd; Brenner, Thorsten; Müller, Marcella C. A.; Juffermans, Nicole P.; Thachil, Jecko (Blood reviews, 2016)
Disseminated intravascular coagulation (DIC) is an acquired thrombo-haemorrhagic disorder which arises in clinical scenarios like sepsis, trauma and malignancies. The clinic-laboratory diagnosis of DIC is made in a patient who develops the combination of laboratory abnormalities in the appropriate clinical scenario. The most common laboratory parameters in this setting have been the clotting profile, platelet count, serum fibrinogen and fibrin degradation markers. These tests had the advantage that they could be performed easily and in most laboratories. However, with the better understanding of the pathophysiology of DIC, in recent years, more specific tests have been suggested to be useful in this setting. The newer tests can also prove to be useful in prognostication in DIC. In addition, they may provide assistance in the selection and monitoring of patients diagnosed with DIC.
Available online 6 November 2015
Gesehen am 28.04.2020